Austria : the essential guide to customs & culture - Gieler, Peter (London : Kuperard, 2018)
Austria has produced some of the world's finest composers, dazzled us with an imperial Baroque architecture, and led the way with groundbreaking psychoanalysis. It has taught us to waltz, defined what a real coffee house is, and given us one of Europe's most popular winter playgrounds. All this from one small nation, roughly the size of South Carolina. Culture smart! Austria describes the real people in the picture postcard, offering key insights into everyday Austrian life and equipping you to discover for yourself the many qualities of this lively people.
Land and people -- Values and attitudes -- Customs and traditions -- Making friends -- The Austrians at home -- Time out -- Travel, health, and safety -- Business briefing -- Communicating.
Includes bibliographical references (page 165) and index.
Keywords: Etiquette -- Austria -- Guidebooks; National characteristics, Austrian; Manners and customs